CONTROLS ON THE GROWTH AND GEOMETRY OF PYROCLASTIC CONSTRUCTS - Riedel C.; Ernst G.G.J.; Riley M. (My University, 2003)
In regions of frequent low-energetic explosive eruptions such as cinder cone fields, ejecta cone forming eruptions are the prime hazard whether from roof collapse or as a hazard to aircraft safety. So, observations and data for ejecta constructs and construct-forming eruptions are systematically reviewed here to help gain insights into key processes involved. Numerical modelling and experiments are developed and complemented by novel analogue granular pile drainage experiments focusing on laboratory 'cinder cones'. Our review shows that the vertical elevation growth rate of cinder cones can be more than 100 m in the first week for intense cone-building eruptions. Ejecta construct grain size is most frequently centred around 10-40 mm, sometimes less. Plinian-style eruption columns, albeit with material substantially coarser than in full-blown plinian eruptions, are commonly observed during the cone-building phase. We show that these observations are not consistent with the classic, no-drag, ballistic model of cone growth and are more consistent with a new model where cones grow by accumulation of clasts falling from an eruption jet column. We also show that cone growth can be equivalently approached either as due to fallout from the margins of a jet or as accumulation obtained by tracking the paths of single particles in the drag case. Numerical experiments are carried out and compare well with morphometric data for ejecta constructs that preserve their primary depositional slope through welding. In the laboratory experiments, granular piles are built up to form a cone and then drained centrally to produce a crater. We explore how the granular pile nature of cones controls crater development and cone geometry. We report and rationalise a close match between experimental and natural cinder cones. Experiments also indicate that an increasing fraction of fine cohesive material accounts for inner crater slopes varying from 45° for cinder cones with little fine ash to near-vertical for ejecta cones rich in fine ash. This could be used in rapid hazard evaluation at little-known, cone-like, pyroclast-dominated volcanoes and in analyses of ejecta constructs on other planets.
Keywords: CINDER CONES; PYROCLASTIC CONSTRUCTS; EXPLOSIVE ERUPTIONS; STROMBOLIAN; LABORATORY EXPERIMENTS; CONE-FORMING ERUPTIONS; VOLCANIC HAZARDS; VOLCANO MORPHOLOGY; ERUPTION MODEL